Perilaku Keberagamaan Masyarakat Perdesaan Pasca Pembangunan PLTA Cisokan di Kabupaten Bandung Barat - Setia, Paelani (Hanifiya: Jurnal Studi Agama-Agama, 2021)
This research examines the religious behavior of the people of Sukaresmi Village, Rongga District, West Bandung Regency after the construction of PLTA Cisokan, West Java. The construction of the Cisokan hydropower plant actually has a negative impact in the form of the destruction of the moral values of the Islamic religion due to the introduction of a new culture into social life. In overcoming this, religion is the key to strengthening awareness of improving the character and morals of rural communities. This awareness was influenced by political and economic dynamics which later manifested itself in an effort to revive religious traditions such as Syahriahan and Manakiban. The success in overcoming the moral decay of society is also influenced by the role of young ulama with broad scientific insight and effective communication. Through field research, interviews and document studies, this research concludes that the homogeneous characteristics of rural communities, including adherence to religion, are factors that facilitate the process of solving problems, including issues of morality and religion.